1969
DOI: 10.1149/1.2411836
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the Composition of the Anodic Layer on the Oxidation Potential of Lead in Sulfuric Acid

Abstract: Potentiostatic oxidations of lead in 1N H2SO4 were performed in the potential range between −900 and +1400 mv (with respect to the mercury/mercury sulfate electrode). The anodic layer was subjected to x‐ray diffraction and chemical analysis. According to the phases present three potential ranges are discerned. From −956 to about −300 mv only PbSO4 is present. From −300 to +900 mv large amounts of PbSO4 and normalPbO‐normaltet are formed as well as small amounts of normalPbO·PbSO4 , 3normalPbO·PbSO4·H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(57 citation statements)
references
References 10 publications
4
53
0
Order By: Relevance
“…According to Giess [8], tin suppresses the transformation of lead to a-PbO. Similar conclusions were derived by Pavlov et al [9] who suggested that Sn is incorporated into the PbO/PbO x crystal lattice. According to Takahashi et al [10] tin accelerates the growth of a-PbO 2 which prevents the formation of a PbSO 4 layer on the surface of the grid.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…According to Giess [8], tin suppresses the transformation of lead to a-PbO. Similar conclusions were derived by Pavlov et al [9] who suggested that Sn is incorporated into the PbO/PbO x crystal lattice. According to Takahashi et al [10] tin accelerates the growth of a-PbO 2 which prevents the formation of a PbSO 4 layer on the surface of the grid.…”
Section: Introductionsupporting
confidence: 62%
“…They also found that PbSn alloys exhibited increased corrosive attack along the grain boundaries at grid-electrolyte interface. As seen from the review of the literature [8][9][10][11][12] addition of Sn leads to increased reversibility and superior charge acceptance. However, it also leads to increased loss of active material due to dissolution of the passive film [11].…”
Section: Introductionmentioning
confidence: 99%
“…15 and from Eq. 2, 3, 9 and our last assumption we can get the following activities on the interface of PbO 9 PbSO~PbSO4 an+ = 10 -6"4s aOH-= 10 -~'ss aso~-= apb 2+ = 1O -3"9 [16] The activities of ions on 3PbO 9 PbS04 . H20/PbO 9 PbS04…”
Section: The Activities Of Ions On Pbo Pbso4/pbs04 Interface--mentioning
confidence: 79%
“…Today this property gives lead cotisiderable use in the chemical industry (3,47). While it is well known that the corrosion resistance is due to thin surface films, these have only been examined in detail in sulfuric acid solutions (48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60) and, to a lesser extent, in hydrochloric acid (61-64).…”
Section: Ia Pourbaix Diagramsmentioning
confidence: 99%